2021
DOI: 10.1101/2021.05.28.21257967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of the Covid-19 vaccines in preventing infection in dental practitioners – results of a cross-sectional ‘questionnaire-based’ survey

Abstract: India started its vaccination program at the beginning of 2021, the main beneficiaries being health workers and frontline workers including police, paramilitary forces, sanitation workers, and disaster management volunteers in the first phase. By the time, the second wave of Covid-19 impacted India, approximately 14 million healthcare and frontline workers, including dentists had been vaccinated. Aim: To study the effectiveness of vaccination on a subset of high-risk healthcare workers i.e. dentists in preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Based on the results, the majority of dentists strongly agreed that vaccination should be mandatory for both citizens and health workers to ensure better health conditions in the current pandemic situation, and the dentists were willing to learn more about the vaccines for their patients' well-being. These results match with other findings that showed that COVID-19 vaccination acceptance is important for maintaining patients' well-being, ensuring the continuity of dental health performance by dentists, and reducing the COVID-19 positivity rate (13). Control of COVID-19 through vaccination is not only dependent on vaccine efficacy and safety.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Based on the results, the majority of dentists strongly agreed that vaccination should be mandatory for both citizens and health workers to ensure better health conditions in the current pandemic situation, and the dentists were willing to learn more about the vaccines for their patients' well-being. These results match with other findings that showed that COVID-19 vaccination acceptance is important for maintaining patients' well-being, ensuring the continuity of dental health performance by dentists, and reducing the COVID-19 positivity rate (13). Control of COVID-19 through vaccination is not only dependent on vaccine efficacy and safety.…”
Section: Discussionsupporting
confidence: 90%
“…However, information regarding the vaccines is still poorly understood, even by health workers, including dentists. This is important, as vaccinated dentists can prevent and/or reduce COVID-19 infection during dental procedures, which is crucial since dentists need to continuously perform dental procedures to make a living (13).…”
Section: Methodsmentioning
confidence: 99%